Dicer induced reactive oxygen species inhibit hepatocellular carcinoma through interacting with cytochrome c oxidase. Issue 1 (31st December 2022) - Hou, Lin; Xing, Na; Yue, Zhao; Wu, Jianhua; Wang, Fujun; Guo, Zhanjun
Abstract: Dicer is an RNaseIII in microRNA processing that modulates multiple biological processes including tumorigenesis. We have shown that Dicer could inhibit the growth of hepatocellular carcinoma (HCC) previously [Zhang L, Wang C, Liu S, Zhao Y, et al. Oncol Lett 2016;11:3961-3966]. Here, we evaluated the relationships between Dicer and reactive oxygen species (ROS) as well as their modulation for HCC. We found Dicer expression was positively associated with ROS generation in HCC tissue at borderline statistical levels ( p = .065 ); functional analysis showed Dicer could both induce the ROS generation ( p < .01) and reduce the activity of Cytochrome c Oxidase (COX) ( p < .05 ) by comparing the Dicer transfected and control HCC cells. The COX inhibitor ADDA-5 hydrochloride could increase the ROS generation, whereas the ROS scavenger N-acetylcysteine (NAC) could decrease the COX activity. Further analysis also demonstrated that one kind of ROS, H2 O2, could repress the proliferation and migration as well as increase the apoptosis of HCC cells. Our data indicated that Dicer could inhibit the HCC growth by promoting ROS generation; ROS and COX interacted with each other to modify this process.